2023
DOI: 10.1021/acsnano.3c04246
|View full text |Cite
|
Sign up to set email alerts
|

An Antisweat Interference and Highly Sensitive Temperature Sensor Based on Poly(3,4-ethylenedioxythiophene)–Poly(styrenesulfonate) Fiber Coated with Polyurethane/Graphene for Real-Time Monitoring of Body Temperature

Wei Fan,
Tong Liu,
Fan Wu
et al.

Abstract: Body temperature is an important indicator of human health. The traditional mercury and medical electronic thermometers have a slow response (≥1 min) and can not be worn for long to achieve continuous temperature monitoring due to their rigidity. In this work, we prepared a skin-core structure polyurethane (PU)/graphene encapsulated poly­(3,4-ethylenedioxythiophene)–poly­(styrenesulfonate) (PEDOT:PSS) temperature-sensitive fiber in one step by combining wet spinning technology with impregnation technology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Meanwhile, the PCOH returns to the original position after experiencing different compressive strains (30%, 60%), which demonstrates the reversibility of strain sensing. PMPχ-SSD sensors possess excellent mechanical and strain sensing capabilities, which enables them to be used for monitoring motion. , A picoammeter was connected to the copper foil on the PMP2-SSD sensor to output different signals through different movements and amplitudes. As shown in Figure d,e, PMP2-SSD sensors could capture signals from different actions, such as stretching, pressing, and twisting.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the PCOH returns to the original position after experiencing different compressive strains (30%, 60%), which demonstrates the reversibility of strain sensing. PMPχ-SSD sensors possess excellent mechanical and strain sensing capabilities, which enables them to be used for monitoring motion. , A picoammeter was connected to the copper foil on the PMP2-SSD sensor to output different signals through different movements and amplitudes. As shown in Figure d,e, PMP2-SSD sensors could capture signals from different actions, such as stretching, pressing, and twisting.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a depicts the structure of the TPFV/CPP yarn, which consists of a carbon fiber conductive layer, PEDOT:PSS (as solid contact, SC), and an ion-selective membrane layer from inside to outside. Poly­(3,4-ethylenedioxythiophene) (PEDOT) is one of the most widely used conductive polymers in sweat sensors, with high capacitance and good electronic conductivity. In the mixed solution of 5 mmol/L K 3 [Fe­(CN) 6 ] and 0.2 mmol/L KCl, the cyclic voltammetric (CV) curves of the carbon fiber and CPP fiber were compared at the same scanning rate (Figure b). The results showed that the CPP fiber showed an obvious reoxidation peak compared with the carbon fiber, implying that the modification of PEDOT:PSS improved the electrical conductivity of the carbon fiber and thus accelerated the electron transfer rate between the electrode and the solution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, researches on wearable electronic devices that can visually monitor individual health and keep track on the progress of patients’ physical recovery in real time have attracted widespread attention. , Wherein, flexible sensors have become one of the major research hotspots due to their ability to maintain excellent conformal contact with human skin, which can be comfortably worn in daily life. , Currently, researchers have developed amounts of flexible sensors based on different mechanisms (capacitive, , resistive, friction electric, , piezoelectric, inductive, etc.). Of these, flexible resistive sensors are considered ideal candidates for next-generation wearable devices due to their relatively simple mechanism of working, tunable mechanical properties, and feasible preparation process .…”
Section: Resultsmentioning
confidence: 99%